A Collection of Swedish Diachronic Word Embedding Models Trained on Historical Newspaper Data. (27th January 2021) - Hengchen, Simon; Tahmasebi, Nina
This paper describes the creation of several word embedding models based on a large collection of diachronic Swedish newspaper material available through Språkbanken Text, the Swedish language bank. This data was produced in the context of Språkbanken Text's continued mission to collaborate with humanities and natural language processing (NLP) researchers and to provide freely available language resources, for the development of state-of-the-art NLP methods and tools.